Combined treatment of cervical pregnancy with methotrexate and prostaglandins. A case report - Raba, Grzegorz; Szczupak, Kamil; Baran, Piotr (European Journal of Clinical and Experimental Medicine, 2014)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Cervical pregnancy is the rarest form of ectopic pregnancy. Resulting from the interaction of the trophoblast-released proteolytic enzymes on the wall of large blood vessels cervical pregnancy may lead to massive, life-threatening haemorrhages. Methods of treatment preserving fertility encompass systemic or local administration of cytotoxic drugs. According to the literature, treatment with systemic application of cytotoxic drugs is ineffective when level of serum hCG is higher than 10000IU/ml. This report presents a case of effective conservative treatment preserving fertility in a woman with cervical pregnancy who had level of serum hCG 74000IU/ml. Clinical effectiveness was achieved by intravenous methotrexate and prostaglandin injections.